Heat and mass transfer in a second grade fluid over a stretching vertical surface in a porous medium - Baoku, Ismail Gboyega; Onifade, Yemi S.; Adebayo, Lateefah; Yusuff, K.M. (Zielona Góra: Uniwersytet Zielonogórski)
The investigation deals with the combined heat and mass transfer in a mixed convection boundary layer flow over a stretching vertical surface in a porous medium filled with a viscoelastic second grade fluid. The partial differential equations governing the model have been transformed by a similarity transformation and the system of coupled-ordinary differential equations is solved by employing the shooting method with the fifth-order Runge-Kutta-Fehlberg iteration technique.
Keywords: heat transfer; mass transfer; second grade fluid; porous medium; stretching surface